Some Remarks on the Origin of the Iranian Stratum of Caucasian Persian (Tati) Lexicon - Artyom Tonoyan (Banber Arevelagitut'yan Instituti)
The Caucasian Persian (Tat), being the only Southwest Iranian language, which is descended from Early New Persian and is spoken in the eastern part of Transcaucasus, is of great interest in the context of the study of the problems related to areal and historical-comparative linguistics, as well as in concern of the revision of issues related to historical contacts and interactions between Iranian languages and peoples in Transcaucasus.